Simultaneous improvement of ketoconazole solubility, antifungal and antibiofilm activity by multicomponent complexation - Zoppi, Ariana (2020)
A novel multicomponent complex (MC) of ketoconazole (KET) with β-cyclodextrin (β-CD) and N-acetylcysteine (NAC) was developed with the purpose of improving the solubility as well as the antifungal and antibiofilm activity of KET against Candida albicans. Results & methodology: The interactions among the components were studied using nuclear magnetic resonance, thermal analysis, powder x-ray diffraction, infrared spectroscopy and scanning electron microscopy. Phase-solubility studies demonstrated a considerable increase in the solubility of the MC. An enhancement in antibiofilm and antifungal activity of MC was determined against C. albicans by XTT assay and microbiological studies. Conclusion: This MC, with improvements in the drug pharmaceutical performance, might have an important potential in the development of new pharmaceutical formulations of KET.